(untitled) - Yutaka, Fujii (Tokyo, 1984)
This publication attempts to present a picture of the Japanese fish processing industry which has gone through many economic and technical changes and reached the present level.
Keywords: Fishery processing,Chế biến thủy sản; Japan,Nhật Bản